2003
DOI: 10.1046/j.0956-7976.2003.psci_1479.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Gaze Direction and the Processing of Facial Displays of Emotion

Abstract: There is good reason to believe that gaze direction and facial displays of emotion share an information value as signals of approach or avoidance. The combination of these cues in the analysis of social communication, however, has been a virtually neglected area of inquiry. Two studies were conducted to test the prediction that direct gaze would facilitate the processing of facially communicated approach-oriented emotions (e.g., anger and joy), whereas averted gaze would facilitate the processing of facially c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

53
490
12
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 495 publications
(566 citation statements)
references
References 15 publications
53
490
12
3
Order By: Relevance
“…While previous studies have shown that gaze direction influences both the perceived intensity of facial expressions (Adams & Kleck 2003;Conway et al 2007) and the reward value of attractive faces (Kampe et al 2001;Jones et al 2006), the effects of gaze direction in these studies were equivalent for judgements of own-sex and opposite-sex faces. Indeed, we know of no studies that have tested whether the strength of preference for direct gaze is modulated not only by the sex of the face judged (opposite-sex versus own-sex) but also by cues to the target individual's emotional state/intentions (unreceptive versus proceptive).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…While previous studies have shown that gaze direction influences both the perceived intensity of facial expressions (Adams & Kleck 2003;Conway et al 2007) and the reward value of attractive faces (Kampe et al 2001;Jones et al 2006), the effects of gaze direction in these studies were equivalent for judgements of own-sex and opposite-sex faces. Indeed, we know of no studies that have tested whether the strength of preference for direct gaze is modulated not only by the sex of the face judged (opposite-sex versus own-sex) but also by cues to the target individual's emotional state/intentions (unreceptive versus proceptive).…”
Section: Introductionmentioning
confidence: 70%
“…Interpreting others' intentions from facial cues may, therefore, require integrating information about the direction of their social attention and their emotional state/intentions (Adams & Kleck 2003;Clark 2005;Jones et al 2006Jones et al , 2007Mishra et al 2007). Indeed, Clark (2005) found that both men and women preferred video clips of proceptive (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, gaze direction seems to modulate the processing of facial expression (Wicker, Perrett, Baron-Cohen, & Decety, 2003). In particular, it has been found that direct gaze enhances the processing of facially communicated approach-oriented emotions (such as anger and joy), whereas averted gaze enhances the processing of facially communicated avoidance-oriented emotions (such as fear and sadness; Adams & Kleck, 2003, 2005. Consequently, the influence of happy and angry expressions might be more pronounced when these expressions are directed towards the observer rather than averted.…”
Section: Methodsmentioning
confidence: 99%
“…In Experiment 2, we aimed at investigating whether this influence differs as a function of whether or not facial expression is explicitly assessed. In addition, considering possible interactions between the processing of facial expression and direction of gaze (Adams & Kleck, 2003, 2005, another goal of our second experiment was to explore whether the influence of expressions on identity memory is modulated by the direction of facial display.…”
mentioning
confidence: 99%